O setor sucroalcooleiro e seus impactos socioeconômicos no maranhão - SILVA, Orlando Guimarães Souza (2024)
The sugarcane and ethanol industry in Brazil has a significant influence, providing opportunities for regional development. Therefore, this study aims to analyze, through a socioeconomic lens, the impacts of the sugarcane agro-industrial system in Maranhão on employment, income, and education. Methodologically, this research is qualitative in nature, with a descriptive character, and seeks to analyze a socioeconomic perspective through the selection of variables that best translate the context and conditions of a specific population or area. To achieve the results, both secondary and primary data were used. The research instrument was an in-depth documentary analysis, based on relevant sources, along a semi structured interview guide conducted with the managers of sugarcane and ethanol plants in Maranhão. The expansion of sugarcane cultivation in Maranhão has significantly influenced the agricultural and socioeconomic landscape of these areas, with a specific emphasis on employment, income, and education. The results indicate a decrease in direct employment in the municipalities, while there was an increase in education levels and workforce qualification; the number of jobs in the sugar-alcohol industrial sector increased, whereas in the agricultural sector it decreased; and that worker wages in Maranhão are higher compared to those in the Northeast.